Psychometric properties of the Portuguese version of the Personality Assessment Inventory: normative data and reliability - Paulino, Mauro; Moniz, Mariana; Moura, Octávio; Rijo, Daniel; Morey, Leslie; Simões, Mário R. (Frontiers in Psychology, 2024)
Introduction Originally published in the United States of America in 1991, the Personality Assessment Inventory (PAI) has been translated and adapted to a growing number of countries, but Portugal had yet to study its adequacy to the Portuguese population. Methods The current study aimed to investigate the Portuguese normative data, the predictive effect of sociodemographic variables on the PAI scores, and the reliability of the Portuguese version of the PAI. Additionally, results were compared with other international versions of the PAI. The sample was comprised of 900 participants (age: M = 43.13, SD = 14.28, range = 18–75), recruited from various regions of Portugal. Results Findings showed that the Portuguese sample scored higher than the U.S. and other international versions of the PAI in most scales. Sociodemographic variables (e.g., gender, age, and educational level) were significant predictors on PAI scores. The internal consistency of the Portuguese sample revealed lower values on the validity scales, but adequate on the clinical, treatment, and interpersonal scales. Overall, the Portuguese PAI revealed adequate psychometric properties, with normative results often superior to other international versions of the inventory. Discussion It is a crucial step into the Portuguese adaptation and validation of this instrument, a measure with considerable potential in clinical, forensic, and research contexts. This adaptation may lead to the growth and development of the psychological assessment field in Portugal, and the opportunity to develop future cross-cultural studies with other international versions of the PAI.